2007
DOI: 10.1001/archotol.133.10.987
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Protective Effect of Pneumococcal Vaccination in Preventing Meningitis After Cochlear Implantation

Abstract: Objectives: To examine if a 23-valent pneumococcal capsular polysaccharide vaccine (PPV23) reduces the risk of meningitis in healthy rats after cochlear implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…In the present study we used unvaccinated animals. Experimental studies showed, that vaccination can protect animals with cochlear implants from meningitis caused by a vaccine-covered serotype of pneumococci (Wei et al, 2007). However this model allows newly Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study we used unvaccinated animals. Experimental studies showed, that vaccination can protect animals with cochlear implants from meningitis caused by a vaccine-covered serotype of pneumococci (Wei et al, 2007). However this model allows newly Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of immunization in reducing the risk of meningitis was tested experimentally by repeating the cochlear implantation experiment on animals that had first been immunized against pneumococcus with a 23-valent polysaccharide vaccine (PPV23) [33]. Although bacteria inoculated by each of the 3 routes caused meningitis in animals with implants that had not received the vaccine, vaccinated animals with implants were protected from meningitis when inoculated via the middle ear ( , by 2-tailed Fisher's exact test) or systemically ( P !…”
Section: Protective Effects Of Pneumococcal Vaccinationmentioning
confidence: 99%
“…The first comprehensive study was published in 2002 [1] after reports about a few cases of death caused by postimplantation purulent meningitis were published. The summary of papers published since 2002 about this phenomenon [2][3][4][5] is that although CI does indeed increase the incidence of otogenic meningitis, this higher risk will, nevertheless, not contraindicate the procedure in light of the existing modern vaccines against meningitis and the advantages of CI--at least not in cases with normal inner ear anatomy.…”
Section: Introductionmentioning
confidence: 99%
“…Torkos et al phatic and CSF spaces are isolated from the middle ear until they are opened by the preparation of a cochleostomy during CI. It is also known that CI performed in ears with normal anatomy increase the risk of bacterial meningitis--this, however, does not contraindicate CI in light of the benefits of implantation, the existence of modern antibiotics and vaccines against meningogenic bacteria [1][2][3][4][5].…”
mentioning
confidence: 99%
See 1 more Smart Citation